HIGH INTENSITY INTERVAL TRAINING (HIIT) LEBIH MENINGKATKAN AMBANG ANAEROBIK DARIPADA STEADY STATE TRAINING PADA SISWA ANGGOTA KELOMPOK EKSTRAKURIKULER ATLETIK LARI JARAK PENDEK - Vidiari J, Indira; Adiatmika, I Putu Gede; Indah S.H. Adiputra, Luh Made; Tirtayasa, K; Muliarta, Made; Griadhi, Adiartha (Sport and Fitness Journal; Volume 5, No.3, 2017DO - 10.24843/spj.2017.v05.i03.p09, 2017)
Anaerobic threshold is the level of oxygen consumption where lactate concentration in blood increasing rapidly and systemic. One of exercises which increase anaerobic threshold is high intensity interval training (HIIT), with training load over anaerobic threshold in a short time and interspersed with active recovery. Another form is steady state training (SST), with training load approaching anaerobic threshold constantly. The purpose of this study to determine differences in the effectiveness of HIIT and SST among students member of short distance running athletic extracurricular groups in Denpasar. This study is pre test and post test experimental group design for 6 weeks and three times a week. Samples included 24 people divided into 2 groups. Group 1 HIIT with the training load of 95% maximum heart rate and Group 2 SST with the training load 80% of maximum heart rate. Measurement of anaerobic threshold by determining Heart Rate Deflection Point (HRDP) according to the Conconi track protocol. The results of the study in both groups obtained subjects 12-16 years old, male, body weight 50-65 kg, height 160-178 cm, and IMT from 16.33 to 22.27 kg / m2. Mean of anaerobic threshold before HIIT training 178.17 ± 2.368 x/minute, while after HIIT increased to 197.83 ± 3.460 x/minute. Mean of anaerobic threshold before SST 177.17 ± 1.586 x/minute, while after SST increased to 185.25 ± 1.288 x/minute. Test of different mean of anaerobic threshold pretest within Group 1 and Group 2 showed that p=0,237 (p>0,05). Test of different mean of increasing anaerobic threshold before and after training in Group 1 and Group 2 using Independent t-Test data test post two groups showed that p = 0.01 (p <0.05). Its concluded HIIT increase anaerobic threshold more than SST among students member of short distance running athletic extracurricular groups in Denpasar. Suggestions for this study are expected coaches able to provide proper training and monitoring methods HRDP evaluation in improving the achievement of athletes.